Evaluating the impact of faculty development programs at the workplace by using reflective critique writing technique - Sarah Amin; Shabana Ali Muhammad; Rahila Yasmeen (BMC Medical Education)
Abstract Background The professional development of faculty members is essential for improving the quality of education. Faculty development programs play a very vital role in continued professional development of faculty. Reflective Critique writing is an important tool for evaluation of faculty development programs, as it provides opportunities for self-reflection, self-critique and self-awareness. The experience of Reflective Critique writing, needs to be explored in order to encourage the faculty to engage in this practice and pursue their personal & professional growth. Aim of study is to determine the effectiveness of Reflective Critique writing in improving the teaching skills of faculty members after a formal faculty development program & to explore their experience using reflective critique technique to improve their professional & personal life. Method It was a mixed method study and design used was Explanatory Sequential Design. Quantitative part is Quasi experimental studies and Qualitative part is Exploratory. Purposive sampling technique was used for Quantitative part (27 faculty members) & Convenience sampling technique (10 faculty members) for Qualitative part of the studies. Case based learning facilitation skills workshop was conducted as a part of faculty development program in which participants were also trained on writing Reflective Critique texts on the “what, so what & now what” model. Participants also went through pre & posttest of the workshop & wrote their first Reflective Critique text. First evaluation for seeing improvement in teaching skills, learning transfer & behavior changes with Reflective Critique writing was carried out after 3 months at workplace (round 1) & second evaluation on the same pattern was carried out after 6 months of workshop at workplace (round 2). Participants wrote 3 Reflective Critique texts in total. At the end of the study, participants experience of Reflective Critique writing was explored in depth by semi-structured interviews of 10 faculty members. Results Results included the grading of reflective capacity of participants on REFLECT rubric & comparison of pre & posttest results. REFLECT rubric grading showed that in 3rd Reflective Critique writing almost 80% of the participants became critical reflectors, improving from an initial 60% progress in first writing, showing the effectiveness of the training program & increased effectiveness of teaching skills, learning transfer & behavior change at workplace. Evaluation was taken up to level 3 of the Kirkpatrick model. Results of pre & posttest showed marked improvement in results with a significant p-value indicating the success of intervention. Hence the data analysis showed the improved teaching skills, enhanced learning transfer at workplace with a positive behavior change which clearly indicated the effectiveness of Reflective Critique in improving the teaching skills of the participants & behavior change at workplace as well as their personal & professional development. Participants experience of Reflective Critique writing was explored further in the qualitative part of the studies and results showed multiple themes including ongoing teaching skills, increased higher order thinking and making sense of experience. Participants labelled Reflective Critique as: The Game Changer. Conclusion Reflective Critique writing enabled the participants to get a deeper critical evaluation of the faculty development program, which in return enhanced their overall performance at workplace.